1983
DOI: 10.1038/sc.1983.48
|View full text |Cite
|
Sign up to set email alerts
|

Systemic humoral factors participating in the course of spinal cord injury

Abstract: Summary. Systemic humoral factors have been studied in traumatic, chronic and acute spinal cord injured patients. Antibodies specific to nervous system auto antigens were detected in a majority of the sera obtained from these patients, at different periods after injury. Limited in vitro sprouting of dorsal root ganglia in chicken embryos was observed in the presence of serum from these patients. The possible association between growth inhibiting factors and the presence of antibodies against nervous tissue aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
32
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 19 publications
4
32
0
Order By: Relevance
“…There is strong evidence for molecular mimicry as a mechanism for induction of these antiganglioside Abs in GBS. Clinical data from multiple sclerosis and GBS imply that anti-ganglioside Abs can also be induced secondary to the nervous system injury (Sadatipour et al, 1998;Press et al, 2001), and some experimental and clinical studies suggest that these Abs can be produced secondary to traumatic injury to the nervous system Mizrachi et al, 1983;Hayes et al, 2002). Regardless of the mechanism of Ab induction, our data suggest that inhibition of axon regeneration may be part of the pathobiological spectrum of circulating autoimmune antiganglioside Abs.…”
Section: Discussionmentioning
confidence: 68%
“…There is strong evidence for molecular mimicry as a mechanism for induction of these antiganglioside Abs in GBS. Clinical data from multiple sclerosis and GBS imply that anti-ganglioside Abs can also be induced secondary to the nervous system injury (Sadatipour et al, 1998;Press et al, 2001), and some experimental and clinical studies suggest that these Abs can be produced secondary to traumatic injury to the nervous system Mizrachi et al, 1983;Hayes et al, 2002). Regardless of the mechanism of Ab induction, our data suggest that inhibition of axon regeneration may be part of the pathobiological spectrum of circulating autoimmune antiganglioside Abs.…”
Section: Discussionmentioning
confidence: 68%
“…Other factors involved in data disparity are level of injury and genetic background; both should be considered and studied in the future. Michal Schwartz's group at the Weizmann Institute of Science provided the first evidence on autoreactive humoral responses against MBP in chronic stages of SCI [6]. They found IgG antibodies against MBP in 68% of the patients with SCI.…”
Section: Discussionmentioning
confidence: 99%
“…The few existing studies have not assessed the humoral and cellular responses in the same group of patients. None of the studies have reported the persistence of a self-reactive response, specifically against MBP, in patients with more than 10 years of injury [5][6][7]. The present work, explored for the first time, the humoral and cellular immune responses against MBP in the same group of individuals.…”
Section: Introductionmentioning
confidence: 96%
“…Less is known about the role played by antibody-producing B cells. In humans with SCI, elevated titers of myelin-reactive antibodies in serum and cerebrospinal fluid (CSF) suggest that SCI activates T and B cells that recognize CNS proteins (10)(11)(12). Using a clinically relevant murine model of SCI, we have shown that SCI induces a long-lasting B cell response, characterized by enhanced lymphopoiesis in bone marrow and spleen, with increased levels of circulating IgM and IgG antibodies (13).…”
Section: Introductionmentioning
confidence: 96%
“…Currently, the breadth of self/auto antigens recognized by SCIinduced antibodies is not known; however, some will bind CNS proteins and the potential exists for antibody-mediated neurodegeneration (10,11,13). Previously, we showed that microinjection of sera containing SCI antibodies into the intact CNS caused focal inflammation and neurotoxicity (13).…”
Section: Introductionmentioning
confidence: 99%